Feeding Level and Frequency Effects in Captive Nile Tilapia (Oreochromis niloticus) Fry - Ibrahim elkhalil Behmene; Benabdallah Bachir Bouiadjra; Sifi Mustapha; Mohamed Daoudi; Abdelkader Homrani (Journal of Aquaculture and Fish Health, 2021)
Hence, the interest in variations in feeding frequencies in captive Nile tilapia fry. Two hundred forty mixed-sex fries, intended to test the feeding frequency, with an initial average weight of 0.03 0.04g; corresponding to an average size of 1.4 cm, randomly distributed in (12) boxes each containing 4 fry/L. Fry are fed with Naturalleva import pellets for 30 days. A single photoperiod is studied for long days (18L: 6D) and to maintain an intensity of 2500 lux. The Statistics data are analyzed using software (R) and tested for normality and homogeneity of variance before being subjected to variance analysis (ANOVA; p≤0.05) and Duncan’s method. A multiple range test was used to compare the mean differences. A feed frequency of 4 times and six (06) times a day shows more efficient use of food than once, twice, and three times a day of food intake. The overall growth parameters for larval tilapia rearing are satisfactory, with the feeding regime set at 35% of the biomass of captive residents for two weeks of rearing, and 17.5% for the remaining two weeks. These results represent standards for the launch of captive breeding of the Nile tilapia strain, which will allow freeing themselves from the often expensive and foreign currency imports of fry for the country.